Employability and intention to apply for rehabilitation in people with back pain: A cross-sectional cohort study - David Fauser; Nadine Schmitt; André Golla; Julia-Marie Zimmer; Wilfried Mau; Matthias Bethge (Medical Journals Sweden, 2020)
Objectives: To analyse the association between self-reported prognosis of employability and health-related measures, and to clarify which determinants influence the intention to apply for medical rehabil-itation. Design: Cross-sectional study of a random sample of German employees. Participants: A total of 6,654 participants (58% female) aged 45-59 years with back pain during the last 3 months. Results: Out of a total of 6,654 persons, 4,838 had a positive self-reported prognosis of employability. Persons with positive and negative prognoses clearly differ with regard to health-related measures. Of 1,816 persons who reported a negative prognosis, 26% stated an intention to apply for rehabilitation. Intention was determined mainly by perceived social support from family and friends (odds ratio (OR) 1.87; 95% confidence interval (95% CI) 1.66-2.10), as well as physicians and therapists (OR 1.64; 95% CI 1.41-1.90). Conclusion: A negative self-reported prognosis of employability is associated with self-reported health restrictions that may determine the need for rehabilitation interventions. A considerable proportion of persons with self-reported health restrictions do not plan to use medical rehabilitation. Perceived social support is an important facilitator of intention to apply for rehabilitation. However, this study needs to be replicated in other populations combining self-reported and administrative data.